Peningkatan Aktivitas dan Hasil Belajar Siswa melalui Pendekatan Inkuiri pada Materi Sistem Perkembangbiakan Tumbuhan dan Hewan di Kelas IX MTsN 3 Aceh Timur - Hafnidar, Hafnidar (Jurnal Aktual Pendidikan Indonesia, 2023)
Education is part of national development which is directed at improving the dignity and quality of human resources. Quality Human Resources (HR) are very important in the development of a nation. The quality of a nation will be determined by its education, only quality human resources will be able to win the world labor market. This research is Classroom Action Research, aiming to determine the increase in student learning achievement through group investigation type cooperative learning on the material "Plant and Animal Breeding Systems", with the research subjects being 28 students in classIX MTsN 3 Aceh Timur for the 2021/2022 academic year. In its implementation, this research consisted of two cycles which included planning, implementation, observation and reflection stages. The results of this research indicate an increase in student learning achievement through group investigation type cooperative learning in cycle I and cycle II, namely with a percentage of 71.43% to 89.28%. This shows that there has been an increase in student learning achievement by 17.85% from cycle I to cycle II. The activities of teachers and students also increased by 17% for teacher activities and 13% for student activities. The average percentage of teacher and student activity in cycle I was 77% and 79% respectively, rising to 94% and 92% in cycle II.